Long-range persistence of daily rainfall in south-western Nigeria - Adegun, Olubunmi (Bulletin of Geography. Physical Geography Series, 2025)
The study analysed the long-range persistence of daily rainfall over south-western Nigeria for the baseline period (1991–2020) and two future periods, 2041–2070, and 2071–2100, representing the mid and late century, respectively. Using the IPSL-CM6A-LR model, the future long-range persistence was estimated for two socio-economic pathways (SSPs), SSP2-4.5 and SSP5-8.5, based on the rescaled adjusted range and modified rescaled range analysis methods. The results of the study indicate that the Hurst exponent is generally expected to be within the range 0.5<H≤1, implying that future daily rainfall is projected to vary between moderately persistent and strongly persistent, with some randomness (H=0.5) expected during the late century under SSP5-8.5. Information on the expected future long-range persistence of rainfall can serve as a useful forecasting tool to enhance sustainable water resources and agricultural management.